High diversity of Pseudo‐nitzschia along the northern coast of Sarawak (Malaysian Borneo), with descriptions of P. bipertita sp. nov. and P. limii sp. nov. (Bacillariophyceae). Issue 6 (14th September 2016) - Teng, Sing Tung; Tan, Suh Nih; Lim, Hong Chang; Dao, Viet Ha; Bates, Stephen S.; Leaw, Chui Pin
Abstract : Forty‐eight isolates of Pseudo ‐ nitzschia species were established from the Miri coast of Sarawak (Malaysian Borneo) and underwent TEM observation and molecular characterization. Ten species were found: P. abrensis, P. batesiana, P. fukuyoi, P. kodamae, P. lundholmiae, P. multistriata, P. pungens, P. subfraudulenta, as well as two additional new morphotypes, herein designated as P. bipertita sp. nov. and P .  limii sp. nov. This is the first report of P. abrensis, P. batesiana, P. kodamae, P. fukuyoi, and P. lundholmiae in coastal waters of Malaysian Borneo. Pseudo‐nitzschia bipertita differs from its congeners by the number of sectors that divide the poroids, densities of band striae, and its cingular band structure. Pseudo‐nitzschia limii, a pseudo‐cryptic species in the P. pseudodelicatissima complex sensu lato, is distinct by having wider proximal and distal mantles, a higher number of striae, and greater poroid height in the striae of the valvocopula. The species were further supported by the phylogenetic reconstructions of the nuclear‐encoded large subunit ribosomal gene and the second internal transcribed spacer. Phylogenetically, P. bipertita clustered with its sister taxa ( P. subpacifica + P. heimii ); P .  limii appears as a sister taxon to P. kodamae and P. hasleana in the ITS2 tree. Pairwise comparison of ITS2 transcripts with its closest relatives revealed the presence of both hemi‐ and compensatory base changes. Toxicity analysis showed detectable levels of domoic acid in  P. abrensis, P. batesiana, P. lundholmiae, and P. subfraudulenta, but both new species tested below the detection limit.